Edward Szymoszek, Ireneusz Żeber , Prawo rzymskie, Wydawnictwo Uniwersytetu Wrocławskiego, Wrocław 2005, ss. 119 - Palmirski, Tomasz (Zeszyty Prawnicze, 2017)
Edward Szymoszek, Ireneusz Żeber , Prawo rzymskie, Wydawnictwo Uniwersytetu Wrocławskiego, Wrocław 2005, ss. 119